Narratives of agency in job burnout recovery - Andreou, Elena (2015)
The present qualitative study investigates the experiences of job burnout recovery and non-recovery concentrating on the role of human agency. This study is additionally interested in workplace change as a component of the recovery process. The four studied individuals had participated and benefited from a rehabilitation that took place two years earlier to conducting the present study, yet their recovery processes after rehabilitation differ greatly from each other. The study utilized a triangulation of analysis methods, using content analysis to recognize the used forms of agency and narrative analysis to examine the individual pathways of recovery or non-recovery. Four narratives were constructed on the basis of the forms of agency that the individuals told to be significant to leading to the current state of the wellbeing: 1) the discovery of personal agency: from workaholism to finding balance, 2) the narrative of non-agency: in the midst of constant change and increasing demands, 3) the narrative of supported agency: from pleading for help to regained joy and spirit and 4) the continuous struggle for support: the burden of excessive responsibility. Forms of agency that were described as significant for recovery were taking responsibility of recovery, changing attitude to work, support received from rehabilitation, health care and family and workplace change. Similarly, forms of agency that hindered recovery were the increasing demands of the workplace and the lack of support from manager and colleagues. These findings show that recovery from job burnout is experienced by the recovering individuals to require an ability to exercise control over themselves and the environment by exercising both personal and proxy agency. Overall this study contributes to the understanding of burnout recovery process by showing its diverse and individual nature. These findings can be further utilized in treatment of job burnout by taking into account individual features and needs in ensuring recovery and recognizing the importance of the ability to exercise control.